Implementasi Peraturan Menteri Dalam Negeri Nomor 70 Tahun 2019 pada Badan Pengelolaan Keuangan Daerah di Aceh Tenggara - Zakaria Zakaria; Zulkarnain Lubis; Adam Adam (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
To analyze how the implementation of the Minister of Home Affairs Regulation Number 70 of 2019 concerning Regional Government Information Systems at the Regional Financial Management Agency in Southeast Aceh Regency, and the factors that hinder the implementation of the Minister of Home Affairs Regulation Number 70 of 2019 concerning Regional Government Information Systems at the Management Agency Regional Finance in Southeast Aceh District.Research data were collected through observation and interviews with key informants, key informants, and additional informants. Further analyzed by qualitative analysis. Based on the results of interviews and observations made by researchers, it was found that there were forms of implementation that were still not in accordance with the Regulation of the Minister of Home Affairs Number 70 of 2019 concerning Regional Government Information Systems. As well as communication indicators that have not run optimally in the context of transmission, clarity, and consistency.